The safety factors for indoor children's amusement center focusing on materials / Nur Ashwini Awang @ Zakaria - Awang @ Zakaria, Nur Ashwini (2021)
According to Korean Academy of Medical Sciences (2020) based on the studies, there are many kinds of rides and play equipment in indoor playground that children can be injured by a variety of materials, such as play equipment, the floor, other people, and furniture . The study will be specified for indoor kids' amusement center in Malaysia. The aim of the study is to focus on the safety aspect requirement for indoor children's amusement centers that focuses on material. The objectives of the research are to determine the safety requirement for indoor children's amusement center focusing on materials and to evaluate the current safety aspects implemented in indoor children's amusement center in Malaysia. Two methods are applicable to this study: Questionnaire and on- site observation by the users and environment at the indoor children’s amusement center at Malaysia. The observation will be conducted at site to identify the actual safety aspects implemented in indoor children's amusement center in Malaysia. The observation will do toward the material in indoor children’s amusement center such as equipment, wall, ceiling and flooring material. After that, questionnaires were distributed to parents or guardians or staff who accompanied their children playing in indoor children’s amusement center. Questions set are all about assessment of interior safety focusing on material aspects that should be considered in the indoor children’s amusement center and which could be perceived by parents while taking their children to the indoor playground. The result of this study showed that safety in indoor children's amusement center meet the safety aspect that were expected by parent. For further studies, the research must make a dipper research in indoor children's amusement center focusing on materials to give an idea or direction to designer or developers about safety requirement for indoor children's amusement center.